Strategi Sekolah dalam Pencegahan Cyberbullying pada Siswa di SMP Negeri 6 Sidoarjo - Ananda Ayu Triwulandari; Oksiana Jatiningsih (Kajian Moral dan Kewarganegaraan, 2023)
Cyberbullying is a new problem in the midst of technological advances. The phenomenon of cyberbullying attacks various groups, especially teenagers.Tteenagers are the highest internet access users so far. In the midst of these technological advances, crime is indeed getting easier to do. The right cyberbullying prevention strategy needs to be done to minimize the occurrence of cyberbullying crimes. If viewed from the hierarchy of needs theory from Abraham Maslow, cyberbullying perpetrators have indications of committing cyberbullying crimes because their hierarchical needs are not fulfilled so they look for other individuals to become targets of cyberbullying victims. From the victim's side, the hierarchical needs that were originally all fulfilled are uprooted, one of which is the need for security. The focus of this research is the school's strategy in preventing cyberbullying on students at SMP Negeri 6 Sidoarjo. The purpose of this study was (1) to describe the school's strategy in preventing cyberbullying in students at the state junior high school 6 Sidoarjo. The theory of thinking in this research is the hierarchy of needs theory from Abraham Maslow. This research uses a qualitative approach with a descriptive Narrative type of research. Techniques in collecting research data using interview techniques, and documentation. The research informants were three vice principals of student affairs as facilitators of change agents, teachers of counseling guidance and facilitators of change agents, representatives of change agents who served as coordinators. The results of the study show that cyberbullying occurs because students do not apply social media ethics and lack of knowledge that perpetrators of cyberbullying can be punished according to applicable laws. Preventing cyberbullying in schools can be overcome through agents of change, Tifa's Teman team, anti-bullying campaign through posters, strengthening collaboration between parents, schools, and peers for the anti-cyberbullying digital literacy movement. Keywords: strategy, cyberbullying, prevention